Comparing Patient-Reported Outcomes From Sham and Saline-Based Placebo Injections for Knee Osteoarthritis: Data From a Randomized Clinical Trial of Lorecivivint. Issue 3 (March 2022) - Tambiah, Jeyanesh R.S.; Simsek, Ismail; Swearingen, Christopher J.; Kennedy, Sarah; Cole, Brian J.; McAlindon, Timothy E.; Yazici, Yusuf
Background: Durable, meaningful symptom responses to intra-articular saline placebo injections are observed in knee osteoarthritis (OA) trials, but it is unclear if these are due to physiological effects. Purpose: To perform a prospective comparison of patient-reported outcome responses among participants with knee OA who underwent intra-articular injection of saline-based placebo or sham (dry needle). Study Design: Randomized controlled trial; Level of evidence, 2. Methods: From a 24-week randomized double-blind trial, participants with moderate to severe knee OA received 2-mL intra-articular injections of saline-based placebo (PBO; 99.45% PBS) or sham (dry needle) to the target knee. Least squares mean differences of changes from baseline to week 24 were compared between the PBO and sham groups for the following: pain Numeric Rating Scale; Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain, stiffness, and function; and patient global assessment. Bang Blinding Index was used to evaluate all-group blinding on day 1 and week 24. Results: In total, 116 and 117 participants were randomized to the PBO and sham groups, respectively. Within the full trial population, the mean ± SD age and body mass index were 59.0 ± 8.5 years and 28.97 ± 4.01, respectively. An overall 406 (58.4%) were female, and 394 (57.3%) had Kellgren-Lawrence grade 3 target knee OA. The PBO and sham groups demonstrated clinically meaningful improvements (≥10%) from baseline in all patient-reported outcomes at all time points (ie, weeks 4-24). Mean differences (95% CI) at week 24 between the PBO and sham groups were as follows: pain Numeric Rating Scale, –0.10 (–0.79 to 0.59; P = .78); WOMAC pain, –2.89 (–9.70 to 3.92; P = .40); WOMAC stiffness, –2.37 (–9.37 to 4.63; P = .51); and WOMAC function, –1.39 (–8.06 to 5.29; P = .68). Bang Blinding Index indicated that blinding was maintained. Conclusion: PBO and sham groups demonstrated equivalent patient-reported outcomes at all time points through week 24, suggesting that responses attributed to saline were contextual (ie, to the procedure) and not physiological. Registration: NCT03122860 (ClinicalTrials.gov identifier).